Optimalisasi Penggunaan Bahasa Indonesia dalam Copywriting Untuk Meningkatkan Engagement di Media Sosial - Chairunnisa, Fadilah; Rianty, Aulia Desty; Shaquille, Rashieka Faizah; Angelita Harefa, Joice Omasi; Siregar, Bona Fergio Fadhil (Fakultas Ilmu Tarbiyah dan Keguruan UIN Sumatera Utara, 2025)
This study is motivated by the importance of language in reinforcing persuasive messages amid the dominance of digital visuals, as well as the limited research on the adaptive use of the Indonesian language in digital communication. The purpose of this research is to examine the optimization of Indonesian language usage in copywriting as a strategy to enhance engagement on social media, particularly Instagram and TikTok. A descriptive qualitative method with a case study approach was employed, involving ten social media accounts representing five categories: health, education, culinary, fashion, and lifestyle. Data were collected through documentation of followers, likes, comments, shares, and views, in addition to an analysis of language styles and the presence of Call to Action (CTA). The findings indicate that variations in language styles, such as storytelling, strong CTA, and proportional code-mixing, are more effective than formal captions. TikTok tends to generate higher engagement per view due to its content distribution algorithm, whereas Instagram demonstrates more stable interactions based on followers. The study concludes that optimizing the use of the Indonesian language in copywriting significantly contributes to audience engagement and the strengthening of brand image.Keywords: copywriting, Indonesian language, engagement, social media